2016
DOI: 10.1016/j.surfcoat.2016.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Alumina-zirconia coatings obtained by suspension plasma spraying from highly concentrated aqueous suspensions

Abstract: Suspension plasma spraying (SPS) deposition represents an innovative technique to produce coatings that exhibit improved properties. However, the key to obtain coatings with superior functional properties relies on the investigation of the suspensions as starting materials. For this reason, the present work deals with the suspension preparation for SPS process and its influence on the resulting coatings.Laboratory-prepared 60/40 wt% alumina-zirconia suspensions were concentrated to avoid energy loss and were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
1
18
0
3
Order By: Relevance
“…Before injection, the suspensions were filtered to remove agglomerates larger than 75 µm. Suspension plasma spraying conditions were as follows: 700 A, 37/8 slpm of argon and hydrogen flow rates respectively, 1.25 m/s torch scan speed, 22 ml/min suspensions flow rate, 40 mm stand-off distance and to further adherence enhancement the substrates were preheated at 573 K. These conditions have been stablished on the basis of previous research [6,29].…”
Section: Coatings Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Before injection, the suspensions were filtered to remove agglomerates larger than 75 µm. Suspension plasma spraying conditions were as follows: 700 A, 37/8 slpm of argon and hydrogen flow rates respectively, 1.25 m/s torch scan speed, 22 ml/min suspensions flow rate, 40 mm stand-off distance and to further adherence enhancement the substrates were preheated at 573 K. These conditions have been stablished on the basis of previous research [6,29].…”
Section: Coatings Preparationmentioning
confidence: 99%
“…As set out in the introduction, multifunctionality of fructose in ceramic processing together with its high compatibility in aqueous suspensions allow to use this saccharide in large amounts in ceramic suspensions. However, the viscosity of the suspension must be kept below certain limits in order not to compromise the feeding of the suspension into the plasma torch as reported elsewhere [29,32]. For this reason, preliminary experimentation was carried out to determine the effect of fructose addition on water viscosity.…”
Section: Establishing An Optimum Range For Fructose Additionmentioning
confidence: 99%
“…. This grey-coloured, melted matrix corresponds to the pseudo eutectic mixture of zirconia and alumina [35], which is distributed throughout the coating.…”
Section: Microstructure Of Coatings Obtained From Diluted Multicomponmentioning
confidence: 99%
“…6)14) For example, Carpio et al 9),12), 14) reported the effects of the spraying distance and supply speed on the properties of sprayed coatings. Rampon et al 7) researched the effects of the viscosity and surface tension of the suspension medium on suspension-sprayed coatings.…”
Section: )4)mentioning
confidence: 99%